Kết quả nghiên cứu di giống rau cau cước (Gracilaria Heteroclada)và rong sụn (Kappaphycus Alvarezii)từ Ninh Thuận để nuôi trồng tại đầm phá Thừa Thiên Huế - Võ, Thị Mai Hương (Bộ Giáo dục và Đào tạo, 2014)
Graci/aria heteroc/ada had ability to optimum grow at 25 - 30 0/00 salinities and 25 300C temperatures. The agar yield, gel streng and chemical compositions were highest at these conditions . In dry season, when the temperature and salinity in the natural lagoon were hight and not very change, this species grew rapidly. But the growth of Graci/aria heteroclada is weaker than the one of Graci/aria tenuistipitata or It died at the low temperatures and salinities. Kappaphycus a/varezii that was cuturedin Thua Thien Hue lagoons has not be able to make hight yeild and hight economical efficiency. These papers also repo rted the influences of concentration NaOH, tempereture and extraction tim e on the agar extract process from Graci/aria heteroc/ada.